Biochemical and Neuroimaging Studies in Subjective Cognitive Decline: Progress and Perspectives. (13th April 2015) - Sun, Yu; Yang, Fu‐Chi; Lin, Ching‐Po; Han, Ying
Summary Neurodegeneration due to Alzheimer's disease (AD) can progress over decades before dementia becomes apparent. Indeed, patients with mild cognitive impairment (MCI) already demonstrate significant lesion loads. In most cases, MCI is preceded by subjective cognitive decline (SCD), which is applied to individuals who have self‐reported memory‐related complaints and has been associated with a higher risk of future cognitive decline and conversion to dementia. Based on the schema of a well‐received model of biomarker dynamics in AD pathogenesis, it has been postulated that SCD symptoms may result from compensatory changes in response to β‐amyloid accumulation and neurodegeneration. Although SCD is considered a prodromal stage of MCI, it is also a common manifestation in old age, independent of AD, and the predictive value of SCD for AD pathology remains controversial. Here, we provide a review focused on the contributions of cross‐sectional and longitudinal analogical studies of biomarkers and neuroimaging evidence in disentangling under what conditions SCD may be attributable to AD pathology. In conclusion, there is promising evidence indicating that clinicians should be able to differentiate pre‐AD SCD based on the presence of pathophysiological biomarkers in cerebrospinal fluid (CSF) and neuroimaging. However, this neuroimaging approach is still at an immature stage without an established rubric of standards. A substantial amount of work remains in terms of replicating recent findings and validating the clinical utility of identifying SCD.